A study on knowledge and practice of mothers of under-five children regarding management of diarrhoea in urban field practice area of MRMC, Kalaburagi, Karnataka, India - Rokkappanavar, Kiran Kumar; Nigudgi, S. R.; Ghooli, Shreeshail (International Journal Of Community Medicine And Public Health, 2017)
Background: Diarrhoea continues to be a major cause of morbidity and mortality among under-five children. Accurate knowledge regarding signs and symptoms, spread, prevention and healthy practices like exclusive breast feeding, immunization, ORS, good sanitary conditions are essential to prevent morbidity and mortality. Study was conducted with an objective of assessing knowledge and practice of mothers of under-five children regarding management of diarrhoea. Methods:A cross-sectional study was carried out from June to August 2015. House to house survey was conducted; a pre-structured and pre-tested questionnaire was administered to all the mothers of under-five children in the study area. Results: A total of 204 mothers were covered. Nearly two thirds (62.74%) mothers were literate and majority of them were in the age group of 21-25 years. More than half of participants lacked adequate knowledge regarding danger signs, spread and prevention. Poor dietary practices were prevalent among 50.49% mothers. Only 50.49% mothers practiced exclusive breast feeding. Nearly one fifth of the mothers practiced bottle feeding, among them only 26.82% practiced hygienic measures. Majority of mothers (55.88%) dispose child’s faeces in open air. Only 43.62% mothers demonstrated proper technique of hand washing. 86.27% participants knew about ORS, among them more than half had adequate knowledge regarding preparation and administration. Only 26.96% mothers dewormed their child regularly. Conclusions:A strong association is found between educational status and appropriate practices regarding diarrhoea management (p<0.001). Hence health education should be used as a tool to promote knowledge and good practice and reduce morbidity & mortality.